Immunohistochemical Analysis of IL-6, IL-8/CXCR2 Axis, Tyrp-STAT-3, and SOCS-3 in Lymph Nodes from Patients with Chronic Lymphocytic Leukemia: Correlation between Microvascular Characteristics and Prognostic Significance. (5th May 2014) - Levidou, Georgia; Sachanas, Sotirios; Pangalis, Gerassimos A.; Kalpadakis, Christina; Yiakoumis, Xanthi; Moschogiannis, Maria; Sepsa, Athanasia; Lakiotaki, Eleftheria; Milionis, Vassilis; Kyrtsonis, Marie-Christine; Vassilakopoulos, Theodoros P.; Tsirkinidis, Pantelis; et al.
Abstract : A number of studies have looked into the pathophysiological role of angiogenesis in CLL, but the results have often been inconsistent. We aimed to gain direct insight into the angiogenic process in lymph nodes involved by CLL, focusing on proangiogenic cytokines and microvessel morphometry. The tissue levels of VEGF, Th-2 cytokines IL-6 and IL-8, IL-8 receptor CXCR2, and tyrosine p-STAT-3/SOCS-3 axis modulating cytokine expression were evaluated immunohistochemically in 62 CLL/SLL cases. Microvascular characteristics were evaluated by image analysis. Results were analyzed with regard to clinicopathological characteristics. Proliferation centers (PCs) were less well vascularised compared to non-PC areas. IL-8 and CXCR2 expression was distinctly uncommon as opposed to IL-6, VEGF and SOCS-3, which were detected in the vast majority of cases. The latter two molecule expressions were more pronounced in the PCs in ∼ 40% of the cases. p-STAT-3 immunoreactivity was recorded in 66.67% of the cases with a predilection for PCs. Microvessel morphometry was unrelated to proangiogenic cytokines, p-STAT-3, SOCS-3, or survival. Microvascular caliber and VEGF expression were higher in Binet stage A, whereasIL-6 expression was higher in stage C. VEGF and p-STAT-3 exerted a favorable effect on progression, which remained significant in multivariate analysis, thereby constituting potential outcome predictors in CLL patients.